Determinants Influencing Purchasing Behavior of Korean Cosmetic Purchasing Intention: Case Study of Thai Female Perspective - Nakpathom, Parinya; Pitchayadejanant, Krittipat; Proces, Jeremy; Chewwasang, Kritta-orn; Channoi , Rachata; Phanpanya, Krit; Tan, Valerie (Community and Social Development Journal, 2022)
This study seeks to explore the main factors influencing Thai female consumers purchasing behavior and identify the relationship between consumer behavior and sales objectives of Korean Cosmetic brands I. The data was collected in the form of an online questionnaire which was divided into 5 subsections. This was followed by 1) Demographic data 2) Thai females purchasing behavior of Korean cosmetics 3) Factors influencing the purchase of Korean cosmetics 4) Purchase intention and 5) Suggestions. Four hundred (N = 400) respondents from Thai females were selected for this study. For data analysis, statistical methods which rely mainly on descriptive statistics and multiple linear regression analysis were used. The multiple linear regression model shows the factors determining buying behavior of Thai females. The results show that Product Packaging, Product Quality, and Price weigh heavily on the purchasing intentions of the participants.